Ferroptosis in gouty arthritis: a potential therapeutic strategy - Yan, Heguo; Xiao, Niqin; Yang, Bo; Zhang, Jian; Xu, Yundong; Chen, Bingbing; Zeng, Sanjin; Qian, He; Zhao, Shengyi; Wang, Rong; Xie, Zhaohu; Li, Zhaofu; et al. (Frontiers in Immunology, 2026)
Ferroptosis, an emerging form of iron-dependent programmed cell death, has recently gained substantial research interest due to its involvement in various inflammatory disorders. Gouty arthritis (GA), a chronic inflammatory disease driven by the deposition of monosodium urate crystals, is characterized by a complex interplay between cell death pathways and inflammatory responses. Despite growing evidence linking ferroptosis to inflammatory regulation, its precise contribution to the onset and progression of GA remains unclear. This systematic review synthesizes current molecular insights into ferroptosis and examines its potential regulatory role in GA pathophysiology. By integrating recent experimental and clinical advances, it evaluates the therapeutic promise of targeting ferroptosis in GA. Through comprehensive analysis of ferroptosis-associated signaling networks and GA-related pathological events, this review aims to provide a stronger mechanistic foundation and highlight future directions for disease research and targeted therapeutic development.